Implementasi Media Papan Pintar Dalam Meningkatkan Motivasi Belajar Anak Usia Dini Di TK IT Darul Qur’an Madani Kota Parepare - Rismayanti03; Tadzkirah (ECEJ : Early Childhood Education Journal, 2025)
This research aims to explore the types of APE used by teachers to foster learning motivation in children, teacher preparation in applying educational game tools to foster motivation and find out in problem solving. There are five types of games on Smart Board media that are used by researchers in learning activities, namely arranging letters, puzzles, bolding words and adjusting images and colors. The aim of children playing is not only to be happy but it is hoped that there is an element of learning in the game, so that an atmosphere of learning while playing is created. Through play, children will learn to know life and gain experiences that bring pleasant impressions to them. This research uses a qualitative descriptive type of research, specifically using a case study approach. Qualitative research is characterized by its descriptive nature and a preference for using inductive analysis.